PEMODELAN BATERAI AIR GARAM DAN PENGUJIAN SALINITAS ELEKTROLIT BERBASIS PLC - Hidayat, Mohammad Noor; Mayrullah, Fahriza; Sapto Wibowo (P3M Politeknik Negeri Banjarmasin, 2022)
One of the technologies of this power source is a brine battery. In this study, testing the effect of electrolyte salinity levels on the performance of brine batteries with two different types of electrodesÂ was carried out, namely using magnesium anodes and aluminum anodes. In its cathode part used inert metal or carbon. Variations are carried out on the electrolyte solution used in the form of brine containing Na and Cl ions as electron conductors as well as reductors. Because the reaction of the brine battery system is relatively complex, a study was conducted in this study to see the effect of electrolyte salinity levels (27, 37, and 47 ppt) on the dc voltage produced. The measured parameters include the value of the dc voltage and the resulting current as well as the change in the salinity level after operating for a certain period of time. Tests were performed on batteries to drain the 0.47Î© resistor load operating for 24 hours non-stop where the parameter measurement setup was performed automatically using a PLC. The values of such parameters are monitored and recorded during 24-hour operation. Based on the results of measurements, the average energy capacity that can be used in Mg electrode cells is 17.6% of the total energy generated from the reaction of battery cells, then the average usable battery capacity on the Al electrode cell is 2.6% of the total energy produced.